The Development of Standardization Parameters of Alstonia scholaris - Goyal, Dr. Swapnil (International Journal of Pharmaceutical & Biological Archive, 2016)
Background: Alstonia scholaris is an important herbal plant. It is commonly used as astringent, rheumatism, antiseptics, anti leprotic, ulcer, and to diverse inflammatory chronic skin diseases, rheumatic pain. general tonic, aphrodisiac, anticholenergic, antidysentery, antipyretic, emmenagogue, vulnerary agents, fatigue, irregular menses, liver disease, dysentery, malaria, diabetes, anthelmintic, Stomachache, skin diseases, swelling, malaria fever, bone fracture, urinary infections. Objective- Present study deals the development of standardization parameters of Alstonia scholaris. Material and method: In the present study, a coarse powder of Alstonia schloaris leaves was prepared by grinding method and standardization parameter were was performed in the laboratory like LOD (Loss of drying), Ash value, Acid insoluble ash, water soluble ash, Extractive value, Solubility test, Phytochemical screening test, U.V. spectrum. Results: The value of physiochemical parameter was calculated. Conclusion: the use of herbal drug are also interrupted due to use of various adulterants so various quantitative and qualitative parameter are use to set the standardization parameter of herbal drugs.This standardization parameters can help to identify and choose appropriate species of selected plants. This parameter also provides information related to purity and efficacy.